Sistem Kendali Otomatis Pada Machine Vision Pengukur Volume Dan Berat - Ihsan, Rizki Al; Arief, Dodi Sofyan; Minarni, Minarni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The advancement of industrial automation technology is growing rapidly. The existence of technology in the computers field, mechatronics allows the creation of automation systems on machine vision. Machine vision is a machine that can obtain information from an image or digital image automatically, taking digital images using a camera and laser in the form of lines, added in the imaging method that obtains 3D images of objects so that the volume of objects can be measured. Laser beam that hits objects and reflected objects form a triangle. In this study, the triangulation method was applied to the machine vision to measure logistics packages. In Indonesia, freight forwarding services measure the volume and weight of objects that are the basis for determining shipping costs. Volume is used as a determinant of costs if the mass is small, while the weight for the large volume. This machine vision tool have functions to measure the volume and weight in the long run which is fast and accurate. In this study, machine vision is desined and built of capable measuring various forms of logistics packages by using a camera and laser beam to record images on a rail connected to a drive motor. The camera moves translatively over the logistical package, when the camera position in the middle of the drive motorbike stops for a moment , the camera will record the image to take the volume of the package and load cell takes load data, then the motor moves back to its original position. Simultaneously the lower motor will drive the driver the package reach the storage area, the motor moves back and forth until the pusher returns to the starting position and the next measurement is carried out. Long wave red laser spctrum, digital camera, microcontroller, triangular measurement method, portable machine. With this mechine vision, the work done by several people will be done with one person, so that it will reduce costs and the time needed will be faster. Keyword : automatic system, motor stepper, microcontroller program